Refugee Migration and Health Challenges for Germany and Europe - Krämer, Alexander; Fischer, Florian (Migration, Minorities and Modernity, 2019)
This book focuses on the closely interlinked areas of refugee migration and health. It discusses the main challenges of the recent unprecedented, extremely diverse and mostly unregulated refugee migration wave for Germany and Europe, and offers a broader view of refugee health from a European perspective. Health issues can lead to several challenges for refugees as well as healthcare providers, and as such the book also examines the requirements for the management of migrant populations in terms of medical care and health system adaptations, and includes theoretical aspects of refugee migration and health as well as various perspectives on the latest developments. Lastly, it describes the healthcare system demands and responses for short- and long-term care of refugees.